Pornograpfi Dalam Perspektif Hukum Islam dan Undang-Undang 44 Tahun 2008 (Suatu kejadian yuridis Normatif) - Ruslan Abdul Ghani (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2010)
This article juxtaposes islamic legal views on pornograpy with positive law pronouncement on the same issue. It specifically explains the nature of MUI fatwa no. 287/ 2001 on pornography by which MUI recommended the state to pass the law againts pornography. it considers MUI's action as preventive measures to protect community pornography and its associented products.